Technological Advancements in Maritime Education: A Collaborative Approach - Diah Zakiah; Bambang Kurniadi; Irfan Wahyunanda; Panderaja Soritua Sijabat; Yusuf Pria Utama; Pesta Veri Ahmadi (Jurnal Penelitian Sekolah Tinggi Transportasi Darat, 2025)
This qualitative research examines the integration of industry professional expertise within maritime engineering education through comprehensive analysis of perspectives from four maritime industry professionals and four academic educators. The study employs descriptive analytical methodology to investigate knowledge transfer effectiveness and technological innovation adoption within maritime engineering education programs. Findings reveal significant gaps between industry competency requirements and current educational outcomes, particularly in practical problem-solving capabilities, technology adaptation skills, and collaborative decision-making competencies. Industry professionals consistently rate educational effectiveness lower than academic educators across critical competency domains, indicating substantial opportunities for improvement through enhanced industry-academia collaboration. The research identifies mentorship programs, collaborative projects, and innovative assessment methodologies as high-impact approaches for addressing educational enhancement opportunities. Technology integration analysis reveals critical gaps between current educational practices and industry technological advancement, emphasizing urgent needs for systematic approaches to maintaining curriculum relevance. The study establishes evidence-based frameworks for sustainable industry-academia collaboration that can enhance maritime engineering education effectiveness while addressing evolving industry competency requirements. Results demonstrate that systematic integration of professional expertise yields measurable improvements in student engagement, graduate employment outcomes, and industry satisfaction with educational programs.